STRUCTURAL AND SEMANTIC CHARACTERIZATION OF THE ENGLISH LANGUAGE TERMINOLOGY IN THE SPHERE OF EDUCATION - Tilavova, Malika (Журнал иностранных языков и лингвистики, 2023)
In this article you will encounter a storm of thoughts about the importance and necessity of using lexical units related to education. Also, the article covers the lexical units of this field, their structural-semantic structure, place of use, necessary information about the history of creation. Today's importance of lexical units related to education in English and Uzbek languages, their relevance according to their study, their place in dictionaries and their useful and harmful aspects for society are revealed.